New approaches to the process industries : the manufacturing plant of the future - Dal Pont, Jean-Pierre; Azzaro-Pantel, Catherine (Control, systems and industrial engineering series., 2014)
Competition from emerging and developing countries, challenges related to energy and water, the continuing increase in the global population and the obligation to be sustainable are all impacting developed countries such as the United States, France, etc. Manufacturing has been almost totally neglected by these developed countries and thus there is a strong need to review R & D and the development and industrialization processes. This is a prerequisite for maintaining and improving welfare and quality of life. The industrialization process can be defined as the process of converting research o.